Subarachnoid diverticulum associated with feline infectious peritonitis in a Siberian cat. Issue 2 (September 2020) - Hoey, Christopher; Nye, George; Fadda, Angela; Bradshaw, Janet; Barker, Emi N
Case summary: A 7-month-old Siberian cat was presented for investigation of acute onset multifocal neurological deficits. Neurological examination documented dull mental status and an ambulatory left hemiparesis. Serum biochemistry documented marked hyperglobulinaemia. MRI of the brain identified marked leptomeningeal contrast enhancement extending along the brainstem caudally to involve the cranial cervical spinal cord. MRI of the cervical spine further identified a subarachnoid diverticulum that extended from the level of the obex to the C2–C3 vertebrae. Cerebrospinal fluid quantitative RT-PCR was positive for the presence of feline coronavirus. Histopathology revealed pyogranulomatous meningitis and choroid plexitis, uveitis and nephritis. Relevance and novel information: This article describes the first reported case of a subarachnoid diverticulum associated with feline infectious peritonitis.